2005
DOI: 10.1021/ja051584d
|View full text |Cite
|
Sign up to set email alerts
|

Diferrous Cyanides as Models for the Fe-only Hydrogenases

Abstract: The first systematic study of diferrous dicyano dithiolates is described. Oxidation of [Fe2(S2C2H4)(CN)2(CO)4](2-) in the presence of cyanide and tertiary phosphines and of Fe2(S2C2H4)(CO)4(PMe3)2 in the presence of cyanide affords a series of diferrous cyanide derivatives that bear a stoichiometric, structural, and electronic relationship to the H(ox)(air) state of the Fe-only hydrogenases. With PPh3 as the trapping ligand, we obtained an unsymmetrical isomer of Fe2(S2C2H4)(mu-CO)(CN)2(PPh3)2(CO)2, as confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 44 publications
1
76
0
Order By: Relevance
“…Each consisted of a face-sharing bioctahedral core, not unlike previous members of this series of diferrous-dithiolates, that is, [Fe 2 (S 2 C 2 H 4 )(mCNMe)(CNMe) 6 ] 2 + , [15] [Fe 2 (S 2 C 2 H 4 )(m-CO)(CNMe) 6 ] 2 + , [22] and [Fe 2 (S 2 C 2 H 4 )(m-CO)(CN) 2 (CO) 2 (PPh 3 ) 2 ]. [23] The Fe À Fe distances fall in the range 2.5135(12)-2.6006(7) , comparable to other diferrous-thiolates as well as the Fe-only hydrogenase active site. [4,26] The bridging CO ligand in 3 and 4 is coordinated in a symmetric fashion, indicated by the similar bond lengths for Fe1ÀC1 and Fe2ÀC1 in each case.…”
Section: X-ray Crystallographymentioning
confidence: 77%
See 3 more Smart Citations
“…Each consisted of a face-sharing bioctahedral core, not unlike previous members of this series of diferrous-dithiolates, that is, [Fe 2 (S 2 C 2 H 4 )(mCNMe)(CNMe) 6 ] 2 + , [15] [Fe 2 (S 2 C 2 H 4 )(m-CO)(CNMe) 6 ] 2 + , [22] and [Fe 2 (S 2 C 2 H 4 )(m-CO)(CN) 2 (CO) 2 (PPh 3 ) 2 ]. [23] The Fe À Fe distances fall in the range 2.5135(12)-2.6006(7) , comparable to other diferrous-thiolates as well as the Fe-only hydrogenase active site. [4,26] The bridging CO ligand in 3 and 4 is coordinated in a symmetric fashion, indicated by the similar bond lengths for Fe1ÀC1 and Fe2ÀC1 in each case.…”
Section: X-ray Crystallographymentioning
confidence: 77%
“…The effect is more pronounced in these two compounds than in the previously reported diferrous-dithiolates, for example, [Fe 2 (S 2 C 2 H 4 )(m-CO)(CN) 2 (CO) 2 (PPh 3 ) 2 ], in which D(FeÀmC) = 0.295 (Table 3). [23] The bending of the m-CO ligands in 5 and 6 is evident from the angles aFe2-C1-O1 of 165.0(4) (5) and 160.0(2)8 (6), which Crabtree [31] has classified as "bent semibridging". [32,33] Cotton described semibridging CO coordination "as a means for a metal atom, otherwise tending to be excessively negative, to transfer electron density to a CO group on a less negatively charged metal atom."…”
Section: X-ray Crystallographymentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, the systematic experimental and computational study of diferrous dicyano dithiolates showed that the oxidation of [Fe 2 (S 2 C 2 H 4 ) (CN) 2 (CO) 4 ] 2− in the presence of cyanide and tertiary phosphines and of Fe 2 (S 2 C 2 H 4 )(CO) 4 (PMe 3 ) 2 in the presence of cyanide affords a series of diferrous cyanide derivatives that bear a stoichiometric, structural, and electronic relationship oxidized state of Fe-only hydrogenases. DFT calculations revealed that the most stable isomers of Fe 2 (S 2 C 2 H 4 )(μ-CO)(CN) 2 (PMe 3 ) 2 (CO) 2 have cyanide trans to μ-CO, an relevant observation to understand the properties of the CO inhibited form of the enzyme [151].…”
Section: Quantum Mechanical Methods In Bioinorganic Chemistry: the Acmentioning
confidence: 99%